2017
DOI: 10.1002/app.44896
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated hydrotalcite‐like materials and their application as thermal stabilizers in poly(vinyl chloride)

Abstract: The preparation of hydrotalcites with traditional materials is often based on the corresponding salts and alkali solutions. In this study, to facilitate industrial synthesis and take advantage of the lower cost during the process, a Ca–Al–HPO3–layered double hydroxide (LDH) was directly synthesized with calcium hydroxide, aluminum hydroxide, and sodium phosphite powders. X‐ray diffraction, Fourier transform infrared, and scanning electron microscopy analyses confirmed the successful synthesis of the phosphite‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…8,9 Every coin has two sides, thus all the thermal stabilities have advantages and disadvantages. 8,16,17 At present, magnalium hydrotalcite as typical Layered Double Hydroxides (LDHs), has been widely used as a high-efficiency long-term stabilizer in calcium and zinc heat stabilization system. 10 Even though organic tin stabilizer conforms to environmental protection, the price is so high that domestic production is quite small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Every coin has two sides, thus all the thermal stabilities have advantages and disadvantages. 8,16,17 At present, magnalium hydrotalcite as typical Layered Double Hydroxides (LDHs), has been widely used as a high-efficiency long-term stabilizer in calcium and zinc heat stabilization system. 10 Even though organic tin stabilizer conforms to environmental protection, the price is so high that domestic production is quite small.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PVC samples are plastified by a double-roller machine and a torque rheometer under a specific temperature usually from 160 to 190 8C for several minutes, the process of which was also a way to mix inorganic products with PVC resin. Sodium stearate (SS) with the formula of CH 3 (CH 2 ) 16 COONa has been identified as a useful surface modifier because of its surfactant property which contains the hydrocarbyl moiety, a hydrophobic group, and could help to integrate well with organic molecular. In addition, owing to the existed H 2 O molecule in interlamination and lots of hydroxyl on the surface, adjacent hydrocalumite particles are easy to band together through hydrogen bond in drying process, thus causing lower heat stability for PVC.…”
Section: Introductionmentioning
confidence: 99%
“…The interlayer guests are known to endow LDHs with predominant effect on the thermos-stabilization of polymer (Zhang et al, 2012;Yan et al, 2017). They enable to capture and react with HCl gas by ion-exchange process, thus achieving the purpose of eliminating HCl catalysis.…”
Section: Importance Of Composition Of Interlayer Guestsmentioning
confidence: 99%
“…The role of LDH additives in absorbing HCl was confirmed experimentally by Ven et al (2000). The reaction mechanism between LDHs and HCl gas proceeds in two steps (Ven et al, 2000;Yan et al, 2017) (Fig. 4): (1) Based on the exchangeability of interlayer guests, the HCl gas reacted with the interlayer guests of LDHs by exchanging the Clions into the interlayer and forming the Cl-intercalated LDHs;…”
mentioning
confidence: 99%
“…Therefore, there are many kinds of hydrotalcites, which have broad application prospects in the fields of adsorption [ 11 ], medicine [ 12 ], catalysis [ 13 ], electrochemistry [ 14 , 15 , 16 ], flame-retardant [ 17 , 18 ], and photochemistry [ 19 ]. Moreover, it can also be used as a heat stabilizer for PVC [ 20 ]. In the 1980s, hydrotalcite was firstly found that when added to PVC materials had better thermal stability than PVC materials without adding hydrotalcite [ 10 ].…”
Section: Introductionmentioning
confidence: 99%